ANALYSIS OF QTC PROLONGATION DUE TO BEDAQUILINE IN TUBERCULOSIS PATIENTS – A RETROSPECTIVE STUDY. - Karelia, Bharti; Singh, Anil; Modi, Saurin (Journal of Biomedical and Pharmaceutical Research, 2021)
Introduction: Bedaquiline should be administered under direct observation along with standard MDR-TB regimen. Recommended dose is 400 mg once daily for 2 weeks followed by 200 mg thrice weekly for 22 weeks. After 24 weeks of Bedaquiline therapy, MDR-TB regimen should be continued as per national TB treatment guidelines. The observed prolongation of the QT interval and potentially fatal cardiac arrhythmia may or may not be related to interference with membrane associated cation transports. Aims and objective: To analyze QTc Prolongation in patients who received Bedaquiline in District tuberculosis center at Rajkot. Material and method: All the patient who received and actively followed and developed QTc prolongation as Adverse Drug Reaction were included in the study. Demographic parameters and detailed information about ECG changes due to QTc Prolongation was noted from patient treatment sheet. Interim analysis was done in this study. Adverse drug reactions data was collected in Adverse Drug Reaction(ADR) form (version 1.3) by Indian Pharmacopoeia Commission. The ADR related data can be accessed through - https://vigiflow-in.who-umc.org. Result: Total 30 patient who received Tablet Bedaquiline were included in the study. Out of which 18 (60%) were males and 12 (40%) were females, Mean age of patient was 28.3 (years) ± 11.6 SD, Mean weight of patient was 48.2 (kg) ± 5.6 SD and 2 patient died due to cardiac arrest. Statistical analysis: Descriptive analysis like mean, standard deviation and percentage was done using excel office version 2016. Conclusion: Long QTc prolongation was noted more among male patients weighing 41 to 50 kg. Among all the participants, majority were having QTc prolongation and two death were observed during treatment of Bedaquiline. The patients will be further followed up for outcome analysis. Keywords: Bedaquiline, QTc interval, adverse effect.